1999
DOI: 10.1046/j.1524-4725.1999.08237.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Upper Lip Wrinkles: A Comparison of 950 μsec Dwell Time Carbon Dioxide Laser with Unoccluded Baker’s Phenol Chemical Peel

Abstract: Treatment of upper lip wrinkles with Baker's phenol resulted in greater improvement than treatment with the 950 microsec dwell time CO2 laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…Although these methods have also yielded excellent results, 1,2 their variable depths of tissue injury have caused some concern. More recently, our group (Chew et al) 21 showed that unoccluded Baker's phenol chemical peel was more effective in the treatment of upper lip wrinkles than a 950 sec dwell time laser in a prospective side-to-side comparison. 19 Several recent studies have prospectively compared CO 2 laser resurfacing with dermabrasion or various chemical peels for scar revision and facial rejuvenation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these methods have also yielded excellent results, 1,2 their variable depths of tissue injury have caused some concern. More recently, our group (Chew et al) 21 showed that unoccluded Baker's phenol chemical peel was more effective in the treatment of upper lip wrinkles than a 950 sec dwell time laser in a prospective side-to-side comparison. 19 Several recent studies have prospectively compared CO 2 laser resurfacing with dermabrasion or various chemical peels for scar revision and facial rejuvenation.…”
Section: Discussionmentioning
confidence: 99%
“…Bis heute gelten Phenol-Peels als der Goldstandard [16,35], an denen sich auch andere Peel-Methoden, wie z. B. Lasermethoden [14], zu messen haben, was die klinischen Ergebnisse und die Einwirktiefe im Verhältnis zur dermalen Lä-sion und anschließenden Regeneration betrifft.…”
Section: > Chemical Peels Sind Eine Effektive Ambulante Methode Zur Hunclassified
“…Die meisten Studien kommen zu dem Ergebnis einer verbesserten Hautstruktur mit einer sichtbaren Straffung und Reduzierung von Fältchen. Insbesondere im Perioralbereich scheint diese Methode im Bereich der Oberlippe [14] (⊡ Abb. 7) und im seitlichen Wangenbereich den Laserpeels überlegen.…”
Section: Indikationenunclassified
“…Die meis ten Stu di en be zie hen sich auf die 7Fal ten re duk ti on und kom men zu dem Er geb nis ei ner sicht ba ren Ver besse rung der Haut struk tur mit ei ner sicht ba ren Straf fung und Re du zie rung von Fält chen. Ins be son de re im Pe ri oral be reich scheint die se Me tho de den La ser peels so gar über le gen [10]. Tie fe Fal ten im Na so la bi al be reich kön nen je doch nicht im mer ge glät tet wer den, erAbb.…”
Section: In DI Ka Tio Nenunclassified